SISTEM INFORMASI E-MARKETPLACE BARANG BEKAS KHUSUS DAERAH YOGYAKARTA - , BAGASTYO ADHI NUGROHO, M. Fakhurrifqi, S.Kom, M.Cs ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lack of online marketplace that provides sell-of service for used goods in the Special Region of Yogyakarta, sometimes make some used goods seller having a hard time to offer their goods. The Information system was built to accommodate used goods seller in the Special Region of Yogyakarta to offer their goods online. Information system of used goods is based on web with PHP as language program, helped by Laravel framework, Javascript with JQuery framework. Apache Webserver, and MySQL for database management system. This information system has a capability to handle data management of used goods, advertisement, and ticket request sent by used goods owner.